EARLY DIAGNOSIS OF CHANGES IN SOIL CHARACTERISTICS OF AREAS SUBJECT TO EROSION IN THE FRAMEWORK OF SOIL AND ENVIRONMENTAL MONITORING - Маматкулова Феруза Абдурашидовна (Journals Park Publishing, 2023)
The article considers the change in climatic conditions and factors affecting the soil-erosion process. Climatic factors are one of the main factors causing erosion processes. Since the object of research is a mountainous region, when considering climatic conditions, it must be taken into account that mountain slopes accumulate atmospheric moisture. But the relief and the relatively insignificant moisture capacity of the rocks that make up them are the reason that this moisture does not remain within the mountainous region, but, obeying the action of gravity, goes to the underlying regions in the form of surface or underground runoff. In addition, an assessment of its role in the process of erosion occurring on the slope lands of southern exposures was considered. Runoff and erosion cause profound soil changes. Since the fall in soil fertility as a result of washout primarily affects the productivity of the territory, the article ends with a clarification of the influence of the degree of soil washout on crop yields. Also, precipitation is one of the main causes of surface runoff in general and storm runoff in particular. "No rainfall, no runoff." In this, the decisive role is played by: the nature of the distribution of precipitation over time, the magnitude of the daily minimum, and the maximum intensity of their precipitation and others.
Keywords: climatic factor, landforms, erosion, soil erosion, precipitation, air temperature.